Intraoperative Near-Infrared Fluorescence Imaging of Multiple Pancreatic Neuroendocrine Tumors: A Case Report. Issue 1 (January 2018) - Handgraaf, Henricus J.M.; Boogerd, Leonora S.F.; Shahbazi Feshtali, Shirin; Fariña Sarasqueta, Arantza; Snel, Marieke; Swijnenburg, Rutger-Jan; Vahrmeijer, Alexander L.; Bonsing, Bert A.; Mieog, J. Sven D.
Abstract : Abstract: Multiple endocrine neoplasia type 1 syndrome can feature pancreatic neuroendocrine lesions that have the potential to degenerate into malignancies (pancreatic neuroendocrine tumors [PNETs]). Resection is required in selected cases and aims to cure patients and to prevent metastasis. Preoperative imaging is important to assess the number, size, and location of PNETs. However, sensitivity of preoperative imaging modalities to detect small lesions can be rather disappointing. This makes intraoperative reassessment of the pancreas crucial. Methylene blue (MB) accumulates in neuroendocrine lesions after intravenous administration. Methylene blue emits fluorescence of approximately 700 nm and can be visualized using a dedicated near-infrared (NIR) fluorescence imaging system. We present a 58-year-old male patient with multiple endocrine neoplasia type 1 syndrome and 2 lesions suspected as PNETs identified during regular follow-up. Intraoperative administration of MB allowed successful NIR fluorescence imaging of multiple lesions missed by preoperative imaging. After confirmation by intraoperative ultrasound, this new finding led to a major change in treatment: from enucleations to total pancreatectomy. Histopathologic examination confirmed that the fluorescent lesions were indeed neuroendocrine lesions ranging from microadenomas to PNETs. This case demonstrates that intraoperative assessment of neuroendocrine lesions can be improved by intraoperative NIR fluorescence imaging using MB, a safe and relatively easy technique. Abstract : Supplemental digital content is available in the text.